Manufacturing Cells for Clinical Use - Weiss, Mark L.; Rao, M. S.; Deans, R.; Czermak, Peter (My University, 2017)
The growth in the number of registered clinical trials indicates that there is a need for cells for many types of cell therapy. Figure 1, which is reprinted from the excellent blog maintained by Alexi Bersenev, shows that the cell type used in most clinical trials worldwide is the mesenchymal stromal cell (MSC). The MSC type requires in vitro expansion to reach a clinical dose and thus there is a desire to optimize and standardize processes and procedures for MSC manufacture specifically for clinical use.
Citation: Weiss, M. L., Rao, M. S., Deans, R., & Czermak, P. (2016). Manufacturing Cells for Clinical Use. Stem Cells International, 5. doi:10.1155/2016/1750697
Keywords: Stromal Cells; Msc; Culture; Cell Biology